Pattern of Antibody Titer Against Salmonella Enterica in Apparently Healthy Individuals - Gupta, Umesh Prasad; Jadhav, Kapilesh; Shrestha, Nischal; Baral, Subash; Parajuli, Amit Kumar; Adhikari, Sandeep (Annals of Clinical Chemistry and Laboratory Medicine, 2018)
Background: Enteric fever is a serious health problem in developing countries including Nepal. Widal test is the routinely used for diagnosis of enteric fever. This study aimed to determine the baseline antibody titers for Salmonella typhi and paratyphi A, B in healthy individuals of Western Region of Nepal. Methods: A total 150 blood samples were collected from the healthy individuals and pattern of antibody titer was measured using standard quantitative tube method. Results: Among 150 blood samples, 103 had shown significant antibody titers (≥ 1:20). The significant proportion (10.7%) of the individuals had anti-O titer ≥ 1:80. Similarly, 86 had anti-H titers of ≥ 1:20 to S. enteric serotype typhi, 23 had a titer of ≥1:80 and 4 had a titer of ≥1:160 respectively. We found 10% and 1.3% for paratyphi A and B, anti-H titers of ≥ 1:20respectively Conclusion: This study concludes that, there should be need to change in the cutoff levels for antibody titer against S. typhi to > 1:80 for both anti-O and anti-H titers for Western Development Region of Nepal.